2011
DOI: 10.1186/1465-9921-12-102
|View full text |Cite
|
Sign up to set email alerts
|

Nasal lavage natural killer cell function is suppressed in smokers after live attenuated influenza virus

Abstract: BackgroundModified function of immune cells in nasal secretions may play a role in the enhanced susceptibility to respiratory viruses that is seen in smokers. Innate immune cells in nasal secretions have largely been characterized by cellular differentials using morphologic criteria alone, which have successfully identified neutrophils as a significant cell population within nasal lavage fluid (NLF) cells. However, flow cytometry may be a superior method to fully characterize NLF immune cells. We therefore cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 54 publications
2
62
0
Order By: Relevance
“…Thus although the anti-NE activity of SLPI is elevated in smokers, secreted SLPI levels in smokers may be altered and nonfunctional in the context of inflammation or infection. This is an important area of study considering that cigarette smoking results in proinflammatory events and impairs anti-IAV response both in vitro and in vivo (20,22,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus although the anti-NE activity of SLPI is elevated in smokers, secreted SLPI levels in smokers may be altered and nonfunctional in the context of inflammation or infection. This is an important area of study considering that cigarette smoking results in proinflammatory events and impairs anti-IAV response both in vitro and in vivo (20,22,36).…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen healthy young adults (9 men, 5 women); 7 nonsmokers (29.2 Ϯ 7.2 yr old) and 7 smokers (27.1 Ϯ 3.3 yr old), as characterized by our previous studies, were recruited to participate in this study (20). Informed consent was obtained from all subjects and the protocol was approved by the University of North Carolina Biomedical Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously demonstrated that CS exposure significantly alters interferon-dependent antiviral responses at the level of the epithelium (19,40). Exposure to CS also alters the ability of epithelial cells to communicate with resident immune cells, such as dendritic cells and Natural Killer (NK) cells in the context of viral infections (17,18). Activation and maturation of NK cells can be modulated by soluble factors released by epithelial cells, such as cytokines/ chemokines, as well as ligands expressed on epithelial cells directly interacting with NK cell surface receptors (5).…”
mentioning
confidence: 99%
“…However, the less invasive procedure of scraping the inferior surface of the inferior nasal turbinate with a Rhino Probe can be performed in these subjects. Third, nasal scrape biopsies can be performed on the same individuals multiple times (usually about 4 weeks in between biopsies) without any significant side effects [28][29][30] . Fourth, NECs are among the first cells to be exposed to inhaled environmental stressors, such as air pollutants, pathogens or allergens and therefore represent valuable in vitro models to study the effects of these stressors on airway epithelial cells.…”
Section: Seed the Cells On Tissue Culture Insertsmentioning
confidence: 99%